Efecto del Flujo Sanguíneo y el Movimiento Corporal en la Variabilidad de las Mediciones de Bioimpedancia - Campo, Daniela; Romero Beltran, Cesar Augusto; Cabrera López, John Jairo; Rodríguez López, Aaron; Mercader Trejo, Flora Emperatriz; Antaño López, René; Larios Durán, Erika Roxana (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Electrical bioimpedance is a technique commonly used to analyze the electrical properties of biological tissues. For this purpose, an alternating electric current signal of controlled magnitude and variable frequency must be applied to the tissue; the measured response corresponds to an electric potential. Several factors can affect the variability of the measurements, in this case, we seek to analyze the effect of blood flow and body movement on this variability, for which measurements were performed in a test subject with the Gamry reference 3000 Potentiostat/Galvanostat, following a 2k experimental design and a standardized measurement protocol. An equivalent circuit was proposed from the data obtained, whose parameters in each case of the study were estimated through an adjustment performed in the Zview software. Average values, standard deviation, and coefficient of variation were obtained for the mentioned parameters. However, the proposed experimental test is insufficient to record the physiological effects of interest, so it is proposed to perform simulations with finite elements to establish better measurement conditions.